Geochemical Processes Leading to the Precipitation of Subglacial Carbonate Crusts at Bossons Glacier, Mont Blanc Massif (French Alps) - Thomazo, Christophe; Buoncristiani, Jean-Francois; Vennin, Emmanuelle; Pellenard, Pierre; Cocquerez, Theophile; Mugnier, Jean L.; Gérard, Emmanuelle (Frontiers in Earth Science, 2017)
Cold climate carbonates can be used as paleoclimatic proxies. The mineralogy and isotopic composition of subglacially precipitated carbonate crusts provide insights into the subglacial conditions and processes occurring at the meltwater-basement rock interface of glaciers. This study documents such crusts discovered on the lee side of a gneissic roche moutonnée at the terminus of the Bossons glacier in the Mont Blanc Massif area (France). The geological context and mineralogical investigations suggest that the Ca used for the precipitation of large crystals of radial fibrous sparite observed in these crusts originated from subglacial chemical weathering of Ca-bearing minerals of the local bedrock (plagioclase and amphibole). Measurements of the carbon and oxygen isotope compositions in the crusts indicate precipitation at, or near to, equilibrium with the basal meltwater under open system conditions during refreezing processes. The homogeneous and low carbonate δ13C values (ca. -11.3‰) imply a large contribution of soil organic carbon to the Bossons subglacial meltwater carbon reservoir at the time of deposition. In addition, organic remains trapped within the subglacially precipitated carbonate crusts give an age of deposition around 6500 years cal BP suggesting that the Mid-Holocene climatic and pedological optima are archived in the Bossons glacier carbonate crusts.